PEMERIKSAAN KEHAMILAN GRATIS DAN PEMERIKSAAN KOLESTEROL, KGD, TEKANAN DARAH DI DUSUN PEMBANGUNAN DESA BAKIUNG. - FIFI RIA NINGSIH SAFARI (Universitas Aufa Royhan Di Kota Padangsidipuan, 2021)
ABSTRACT Health development is essentially an effort carried out by all components of the Indonesian nation which aims to increase awareness, willingness and ability to live healthy for everyone in order to realize the highest degree of public health, as an investment for the development of socially and economically productive human resources. economical. The success of health development is largely determined by the continuity between program and sector efforts, as well as continuity with the efforts that have been implemented in the previous period. Based on the background that has been described, the problem is the lack of health checks in the community. The approach taken to solve the problem is an individual and classical approach. With the free pregnancy check-ups and checks for cholesterol, KGD, and blood pressure, I hope that all pregnant women and the public always check their health at the puskesmas and health workers in the neighborhood where pregnant women and the community live.